2014
DOI: 10.1371/journal.pone.0088227
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Fatty Acid Receptor GPR120 in the Gut of Diet-Induced-Obese Rats and Its Role in GLP-1 Secretion

Abstract: Stimulation of the G protein coupled receptor GPR120 has been shown to have anti-inflammatory and insulin-sensitizing effects, to promote glucagon like peptide-1 (GLP-1) secretion, and to play a key role in sensing dietary fat and control energy balance. In a search for differentially expressed genes potentially involved in food intake and body-weight regulation we identified GPR120 to be differentially regulated in the intestine of selectively bred diet induced obese (DIO) and diet resistant (DR) rats. Subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 13 publications
4
37
1
1
Order By: Relevance
“…Interestingly, while agonism of FFAR4 with n-3 PUFA has clearly been shown to increase GLP-1 secretion from rodent and human intestinal L-cell lines [78], the in vivo effects of FFAR4 on GLP-1 secretion have been less poorly resolved. While some studies have shown that n-3 PUFA such as ALA and DHA increase plasma GLP-1 levels in vivo [7, 18], the physiological relevance of FFAR4 in this role have been challenged by other studies that have shown that FFAR4 agonism by ALA does not play a major role in increasing plasma GLP-1 levels in vivo in rats [13], as well as those that point to a contribution of the related FFAR1 in modulating the GLP-1 secretagogue effect of PUFA in vivo [19]. Here, we did not observe any alterations in GLP-1 concentrations in animals fed FO or FSO diets compared to those fed CON diets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, while agonism of FFAR4 with n-3 PUFA has clearly been shown to increase GLP-1 secretion from rodent and human intestinal L-cell lines [78], the in vivo effects of FFAR4 on GLP-1 secretion have been less poorly resolved. While some studies have shown that n-3 PUFA such as ALA and DHA increase plasma GLP-1 levels in vivo [7, 18], the physiological relevance of FFAR4 in this role have been challenged by other studies that have shown that FFAR4 agonism by ALA does not play a major role in increasing plasma GLP-1 levels in vivo in rats [13], as well as those that point to a contribution of the related FFAR1 in modulating the GLP-1 secretagogue effect of PUFA in vivo [19]. Here, we did not observe any alterations in GLP-1 concentrations in animals fed FO or FSO diets compared to those fed CON diets.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, epididymal adipose of mice fed high-fat diets with variable n-6:n-3 ratios ranging from 1:1 to 20:1 showed significantly lower levels of FFAR4 expression, and also had significantly higher levels of inflammatory mediators such as TNF-α and IL-10 compared to control-diet fed mice, suggesting that the n-6 and n-3 components of fats make important contributions toward both inflammation and expression of FFAR4 [12]. Similarly evidence exists in rats, where energy-dense, high-fat diets were found to increase expression of intestinal FFAR4 in a diet-induced obese (DIO) rat model as early as 6 months of age [13]. Interestingly, others have showed that the effects of high-fat diet on FFAR4 expression are tissue specific, as rats fed a high-fat diet for 12 weeks showed upregulation in FFAR4 expression in cardiac tissue and extensor digitorum longus (EDL) skeletal muscle, but not in liver or soleus skeletal muscle [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the gastrointestinal system, FFA4 receptor is expressed in the intestinal endocrine cell lines STC-1 and GluTag (Tsukahara et al, 2015), GIP-secreting K cells (Parker et al, 2009), stomach ghrelin-secreting SG-1 and MNG-1 cells (Lu et al, 2012), and dietary fat sensor epithelial cells (Paulsen et al, 2014). Previous studies have suggested that FFA4 receptor is involved in sensing the fat and regulation of hormone secretions such as GLP-1, GIP or CCK in these cells; however, the administration of the cpdA for a short duration (a newly identified synthetic FFA4 receptor agonist) did not cause significant GLP-1 secretion in enteroendocrine L cells (Oh da et al, 2014).…”
Section: Expression and Functions Of Ffa4 Receptormentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The receptor was proposed as a possible antidiabetic and antiobesity target for the first time in 2005 when it was reported to be expressed in the intestinal tract and activated by dietary free fatty acids to stimulate incretin secretion, 8 although this property of the receptor remains controversial. 9 FFA4 was subsequently found also to be expressed in macrophages, liver and adipose tissue, and to mediate antiinflammatory and insulin sensitizing effects. 10 The report that mice lacking FFA4 develop obesity, insulin intolerance and fatty liver when fed a high-fat diet and that a human population with a dysfunctional FFA4 variant has an increased risk of obesity supported a significant role of the receptor in metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%